THE EFFECT OF TEACHER’S WRITTEN FEEDBACKS ON INDONESIAN EFL LEARNERS’ RECOUNT WRITING COMPETENCE - Marwito Wihadi; Ine Martiana (Indonesian EFL Journal, 2015)
This paper investigated the effect of teacher’s written feedbacks in recount writing competence and the students’ attitudes towards written feedbacks. Giving written feedbacks helps students to decrease their errors and gives guidance in writing as a beginner writer. This study employed a quantitaive and qualitative research design. The experimental group given written feedbacks. For measuring the effect of written feedbacks, a pretest and posttest was administered to both group. Meanwhile, for getting their attitudes toward teacher’s written feedbacks was administered questionnaire and open-ended interview. Based on the data, teacher’s written feedbacks gave positive effects on their improvement in recount writing competence. The result of questionnaire and interview showed that students got real guidance and special attention individually in their writing process as a beginner writer.Keywords: written feedbacks, recount writing competence, attitudes.